Identification of the class of secondary metabolites of Fruit Extract ethanolic Solanum acanthodes Hook and its potential on fungicidal Candida albicans in vitro - Lima, Renato Abreu; Gomes, Auricélia Diogenes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study aimed to identify the classes of secondary metabolites from the ethanol extract of fruits of Solanum acanthodes and evaluate the fungicidal activity against Candida albicans in vitro. We carried out the identification of secondary metabolites with crude plant extract and chromatography test to identify potential substances in the ethanol extract as substances isolated patterns of other species of Solanum. For the test fungicide used the technique of fusion disc. For positive control, we used discs without the plant extract and as a negative control discs with emulsifying chemical Kasumin®. The design was completely randomized with three replicates per treatment. The evaluation consisted of checking the growth of fungus, every 24 hours for six days, measuring the colonies. Data were subjected to analysis of variance and means were compared by Tukey test at 5%. Regarding the recognition of secondary metabolites from the ethanol extract of the fruits of S. acanthodes tests, the presence of alkaloids, cardiac glycosides, coumarins, tannins, triterpenes and free antracênicos derivatives was found. However, the results were negative for flavonoids. In chromatographic technique it was possible to identify the glycoalkaloid solasodine. After 144 hours, noted that the ethanol extract of the fruits of S. acanthodes showed satisfactory results of C. albicans, which occurred inhibition of fungal growth (average 2.4 mm) demonstrating greater inhibitory spectrum compared to the chemical (average 3 4mm). We conclude that S. acanthodes presents secondary metabolites and that these had a direct relationship in the inhibition of growth of C. albicans, but new methods and concentrations need to be tested.